Critical behavior of models with infinitely many absorbing states - Mendes,J.F.F. (2000)
In this article we review several models with many absorbing configurations. In all these models attention will be focused on the in uence of the initial state on the dynamic evolution. The relation of systems with many absorbing configurations to those displaying avalanches (self-organized criticality) is also investigated. Some new results are presented both for systems with and without parity conservation. Recently derived scaling relations are tested.